PENGEMBANGAN PERANGKAT LUNAK SISTEM INFORMASI GEOGRAFIS BERBASIS WEB - Budi Santosa (Jurusan Teknik Informatika, 2011)
Geospatial information is currently not only can be displayed using GIS software in a stand alone but can use the Internet as a medium for distributing geospatial information. Through the internet the whole population in the world can access geospatial information and provides a medium for geographic information processing desired without being limited by location. Web-based GIS map evolved from a web and client server architecture for distributed into a unity. Internet technology provides a new form for all functions of information systems is data collection, data storage, data retrieval (retrieving), data analysis and visualization of data. In this paper, the latest technology, web-based GIS with emphasis on architecture and stage of development of web-based GIS software that starts from the needs analysis to the maintenance stage. The implementation phase of the development of web-based GIS software to produce a web-based GIS product is right with the right process as well.